MENINGKATKAN HASIL BELAJAR SISWA MELALUI GAME PUZZLE MATA PELAJARAN PPKn KELAS III SEKOLAH DASAR - Paulangan, Cahyani; Adam, Andi; Jaya, Setiawan Uthama (Universitas Tanjungpura, 2024)
This research is a Classroom Action Research (CAR) which aims to determine the improvement in student learning outcomes through puzzle games for PPKn subjects for grade III elementary schools.. The subjects in this research were 20 students in class III of SD Inpres Tinggimae for the 2023/2024 academic year, consisting of 8 boys and 12 girls. Data collection techniques use observation and tests. The instruments of this research are observation sheets and test sheets. The data analysis technique is descriptive qualitative. The results of the research show that using puzzle games can improve the learning outcomes of class III students at SD Inpres Tinggimae. The increase in student learning outcomes can be seen from the value of learning outcomes in the first cycle of students who reached the KKM as many as 4 students or 20%, while in the second cycle there were 19 students or 95%. Therefore, it can be concluded that by applying puzzle games to the learning of Pancasila and Citizenship Education, students can improve classical learning outcomes and achieve success criteria.